2019
DOI: 10.1111/1750-3841.14792
|View full text |Cite|
|
Sign up to set email alerts
|

Food Consumer Behavior and Salmonella Exposure Self‐Perception in the Central Region of Mexico

Abstract: In Mexico, there is limited information regarding food consumer behaviors at home. The knowledge of food consumption and food handling practices can help to determine more realistically the exposure to different hazards, such as Salmonella spp. on the population. The main goal of this study was to characterize the food consumption habits of five food groups (fruits and vegetables, fresh meat, dairy products, processed meat products, and seafood), food handling practices, and Salmonella exposure self‐perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Murray and Glass-Kaastra [34] showed that the majority of respondents are aware of the risks of foodborne illness associated with chickens, and the majority are aware that chickens that are not fully cooked can be a cause of foodborne illness. A study in Mexico showed that fresh meat is the most commonly considered sources of salmonellosis compared to other food categories, such as "fruits and vegetables" or "dairy products" [39]. In an Italian study, on the other hand, the awareness of Salmonella transmission was not particularly high.…”
Section: Discussionmentioning
confidence: 95%
“…Murray and Glass-Kaastra [34] showed that the majority of respondents are aware of the risks of foodborne illness associated with chickens, and the majority are aware that chickens that are not fully cooked can be a cause of foodborne illness. A study in Mexico showed that fresh meat is the most commonly considered sources of salmonellosis compared to other food categories, such as "fruits and vegetables" or "dairy products" [39]. In an Italian study, on the other hand, the awareness of Salmonella transmission was not particularly high.…”
Section: Discussionmentioning
confidence: 95%
“…Table 5 shows the per capita consumption (mean and 90% credible interval) of different food products for the population of the Central Region of Mexico estimated in a previous study of our group (Godinez‐Oviedo et al., 2019). The most consumed products included most of the fruit and vegetable categories (citric fruits, seed fruits, tropical fruits, berries, stem vegetables, roots and tuber, fruit vegetables, inflorescence vegetables) (39.98–56.55 kg/year), milk (48.02 kg/year), and yogurt (37.86 kg/year).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 25 food products were grouped into five food categories described in a previous study (Godínez‐Oviedo et al., 2019). The food categories included (i) fresh meat (beef, chicken, pork, and turkey); (ii) processed meat products (bacon, ham, Mexican chorizo, and sausage); (iii) (fresh fruits and vegetables (citrus fruits [e.g., orange, lemon, tangerine], seed fruits [e.g., apple, pear, quince], tropical fruits [e.g., avocado, mango, papaya], berries [e.g., strawberry, blackberry, raspberry], tuber, bulb, and root vegetables [e.g., carrot, potato, onion], leafy greens [e.g., lettuce, spinach, parsley], inflorescence vegetables [e.g., broccoli, cauliflower], and fruit vegetables [e.g., tomato, chili, cucumber]), and dried fruits/nuts (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mexico, Salmonella infections are of great concern for the Ministry of Health, with 70,000 reported cases each year and 42.76% of isolated Salmonella strains coming from foods of animal origin, mainly from pork, beef, and chicken (Contreras‐Soto et al, 2019). Although the public health burden caused by Salmonella is evident, information on specific pathogen‐food source association is lacking (Godínez‐Oviedo, Parra, Vergara, González, & Iturriaga, 2019). In two of the few studies where a wide range of food products were sampled, RTE meat products are mentioned as some of the most contaminated after raw meat and raw meat products like economical chorizos (Charles‐Hernández, Medina‐Solís & Hernández‐Romano, 2007; Gutiérrez‐Cogco, Montiel‐Vásquez, Aguilera‐Pérez, & González‐Andrade, 2000).…”
Section: Introductionmentioning
confidence: 99%